Os fundamentos de legitimidade do direito político em Rousseau - Roman, Jaqueline Fátima (2011)
This work aims to investigate what are the legitimacy foundations of political law in the thoughts of Jean Jacques Rousseau. For the Geneva-born philosopher, the man is not a political being by nature, as politics is directly related to social life. Only in the social state it is possible to talk about such law. However, the present work starts with the study of the state of nature, and eventually it will approach the social state. This is justified by the fact that it is in this state that Rousseau, through the hypothetical natural man, builds the idea of what he considers to be a reference of human being. Leaning on the natural man, he finds arguments to differ artificial and natural features of man. The study of the state of nature is also important because in it there are feelings that will be necessary to form a society founded on the legitimate political law, as it is the case of love of oneself. This might be the starting point to understand the legitimacy foundation in Rousseau s political law. Starting from the study of the differences between the state of nature and the social state, it is possible to show why the pact between rich and poor, founded on the inequality, is considered illegitimate by Rousseau, and also reason about the necessary political foundations for the building of a legitimate civil pact. What are the necessary conditions for the man to live in society as free as before? In Rousseau s point of view, the man cannot renounce his freedom; otherwise he will lose his human condition, as each man has the same value as the others from his species, and therefore cannot dominate or obey others. Thus, a civil pact similar to the pact between rich and poor is completely illegitimate to Rousseau because it allows the domination of a man over another, denaturalizing him. The free man is the one that obeys only his own will. But how can we envisage life in society with the obedience of solely one s own will, that is, from what reference is it possible to found a legitimate pact and, consequently, Political Law? To solve this problem, our philosopher proposes a new civil pact, and in it the idea of popular sovereignty: people reunited in assembly are the only legitimate sovereign and apt to approve laws which they have to obey. These laws must be in accordance with the general will, which aims at the common well-being and the public utility. That way, each man votes according to his conscience, without any influences, and obeys only his own will, which is consequently reflected in the laws he has approved. Therefore, a man cannot relegate to a representative the power to approve laws, because the exercise of sovereignty is inalienable. This is the legitimate way that Rousseau found for the man to obey but not to serve.